Analisis 10 Elemen Sistem Manajemen Keselamatan PO MTS - Hanendyo Putro; Siti Shofiah; Suprapto Hadi; Kanindia Maulidhany (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
This study aims to determine the implementation, constraints, efforts in implementing the Safety Management System (SMK) at PO MTS. This study uses 10 elements of SMK. Qualitative descriptive method with supporting data using instruments, observation, guttman scale interviews. The guttman scale value is 95% which means it exceeds 50% so that it can be stated that the data obtained is complete. The results of the study show that 8 elements of SMK have implemented PO MTS, while elements 9 and 10 have not been implemented. This study has proposed design elements 9 and 10 to improve SMK PO MTS. The design is adjusted to the regulations and requirements of PM 85 of 2018 to overcome obstacles in implementing these elements.